Understanding and Managing Caesarean Scar Ectopic Pregnancy: A Retrospective Analysis of Risk Factors, Strategies, and Outcomes - Aldawsari, Abdullah; Al-hussaini, Heba (Clinical Journal of Obstetrics and Gynecology, 2024)
Objective: Caesarean Scar Ectopic Pregnancies (CSEP) pose distinct diagnostic and management challenges. This study investigates the risk factors, treatment options, and outcomes for CSEP cases treated at Prince Sultan Medical Military City, Riyadh. Methods: Over a two-year period, medical records of 28 patients with CSEP were reviewed, collecting data on patient demographics, obstetric history, and treatment outcomes. This analysis aimed to identify influential risk factors and assess the effectiveness of various management strategies. Results: Treatment success was achieved in 85.7% of cases, with Methotrexate (MTX) proving effective in over half of the cases. The findings suggest significant risk factors and best practices for managing this rare condition. Conclusion: Early detection, risk factor awareness, and tailored treatment strategies are key to optimizing outcomes in patients with CSEP.